Knowledge, attitude, and practice towards e-cigarettes among adults in the Kingdom of Saudi Arabia: a cross-sectional study - Alhemayed, Rahaf Saad; Al-Hanawi, Mohammed Khaled (Frontiers in Public Health, 2025)
BackgroundAmid increasing evidence of the health risks linked to traditional combustible cigarettes, electronic cigarettes (e-cigarettes) have become widely adopted. However, the rise in e-cigarette use also poses emerging health risks. This study examines the knowledge, attitudes, and practices (KAP) related to e-cigarette use among the general population in Saudi Arabia.MethodsThis cross-sectional study collected data through a structured, self-administered online questionnaire from 1,233 participants during the period from 10 April 2025 to 4 May 2025. Descriptive statistics, including frequencies and percentages, were used to summarise participants’ demographic and socio-economic characteristics. Chi-square (χ2) tests were used to examine the bivariate associations between socio-demographic variables and each KAP domain. Additionally, multivariable logistic regression analyses were performed to examine factors associated with sufficient knowledge, positive attitudes, and positive practices regarding e-cigarette use.ResultsThe mean knowledge score was 9.50 (SD = 3.49, range: 0–15), with approximately two-thirds of the sample (n = 819) classified as having sufficient knowledge. The mean attitude score was 23.96 (SD = 6.68, range: 9–35), with 59% of the sample (n = 731) exhibiting a positive attitude. The mean practice score was 1.56 (SD = 1.09, range: 0–3), with less than half the sample demonstrating positive practice. Participants with sufficient knowledge were over twice as likely to hold a positive attitude [adjusted odds ratio (AOR) = 2.156; 95% confidence interval (CI): 1.509–3.080; p < 0.01], while both sufficient knowledge (AOR = 2.195; 95% CI: 1.343–3.589; p < 0.01) and a positive attitude (AOR = 13.842; 95% CI: 8.190–23.396; p < 0.01) strongly associated with positive practices.ConclusionThis study demonstrated positive correlations among knowledge, attitude, and practice of e-cigarettes, emphasising that tailored, nationwide awareness campaigns addressing diverse socio-demographic profiles can improve knowledge, modify attitudes, and ultimately reduce e-cigarette use.